From Andalusia to Modern Europe: Tracing of Islamic Cultural Heritage and Its Educational Influence on Religious Moderation in Indonesia - Ifrak, Karim; Anggraeni, Dewi; Jaeni, Muhamad; Irfanullah, Gumilar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This article explores the cultural heritage of Islam in Andalusia and its role in religious moderation education in Indonesia. This qualitative research uses a historical approach and implementative analysis through the study of texts, history and related themes, by exploring the historical role of Andalusia as a center for inter-religious intellectual exchange. The results of this research reveal that: 1) the Islamic cultural heritage in Andalusia is a center of intellectual activity that combines various interdisciplinary scientific traditions and multicultural values ​​of tolerance from Islam, Christianity and Judaism, which has a significant and sustainable impact in modern Europe; 2) the concept of convivencia practiced in Andalusia depicts Muslims, Christians and Jews living together in an atmosphere of mutual respect and collaboration, thus giving birth to a civilization rich in various traditions; and 3) the Islamic cultural heritage in Andalusia not only contributes to intellectual progress in Europe, but also provides valuable insights for Indonesia in building an inclusive and tolerant education system to strengthening Religious Moderation. This research implies that the developing intellectual heritage in Andalusia contributes to the strengthening of scientific traditions and encourages respect for diversity and intercultural dialogue in a multicultural society.